2015
DOI: 10.1589/jpts.27.3413
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mechanical massage on early outcome after total knee arthroplasty: a pilot study

Abstract: [Purpose] The aim of this study was to evaluate the efficacy of mechanical massage via Endermologie® after total knee arthroplasty in reducing edema and pain and improving knee range of motion, in the early postoperative period. [Subjects and Methods] Eighteen patients with knee edema following total knee arthroplasty were randomly assigned to the intervention group (n=8) or the control group (n=10). The intervention group received mechanical massage therapy using Endermologie® and the control group received c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, it is well known that the pain experienced by patients after TKA can be so severe that they are unable to concentrate during exercise, and muscle weakness secondary to pain is a barrier to early rehabilitation [ 14 ]. Physical therapists should implement interventions to help patients with early post-arthroplasty pain and improve their physical function, such as strength and range of motion, which can lead to long-term benefits for future patients, such as improved gait speed [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that the pain experienced by patients after TKA can be so severe that they are unable to concentrate during exercise, and muscle weakness secondary to pain is a barrier to early rehabilitation [ 14 ]. Physical therapists should implement interventions to help patients with early post-arthroplasty pain and improve their physical function, such as strength and range of motion, which can lead to long-term benefits for future patients, such as improved gait speed [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are still many patients with early postoperative flexion pain that causes joint stiffness. Kim et al once used the French endermologie method to massage the quadriceps of patients after knee replacement and found that can relieve pain [ 10 ]. Self-massage by patients also can improve the range of flexion motion of the knee joint [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Massage on the neck muscles extends the range of cervical spine rotation7 ) and improves neck flexor muscles8 ) . In addition, massage after total knee arthroplasty decreases pain and increases the diarthrodial range9 ) . In the current study, 10 to 20 minutes were determined to be appropriate for a scalp massage6 ) .…”
Section: Introductionmentioning
confidence: 99%